Trends and Evolution of Digital Accounting Research: A Bibliometric Analysis Using VOSviewer - Nur Ismanidar; Tengku Putri Lindung Bulan; Ahmad Ridha (Jurnal Investasi Islam, 2026)
This study aims to map the development and trends in digital accounting and digital transformation research through bibliometric analysis. Data were retrieved from the Scopus database covering the period 2007–2025 and analyzed using VOSviewer software. After a screening process, 233 journal articles were selected and examined to review publication trends, subject-area distribution, author collaboration, and keyword mapping. The findings reveal a significant surge in publications since 2020, with major contributions from Business, Management & Accounting (20.3%) and Computer Science (20%), followed by Social Sciences, Economics, and Engineering. Keyword analysis identified seven main clusters: digital transformation, artificial intelligence, blockchain, digital literacy, accounting analytics, gender, and ERP/cloud systems. The results highlight the multidisciplinary nature of digital accounting research and its growing relevance in supporting transparency, efficiency, and innovation in business. This study contributes by proposing a roadmap for global research, offering guidance for academics, practitioners, and policymakers, while suggesting directions for future studies.